Incorporação de clorexidina em diferentes cimentos de ionômero de vidro: microdureza superficial e MEV - Hirata, Francielle Carneiro (2020)
Objective: To evaluate the effect of adding chlorhexidine digluconate (CHX) to the liquid of the glass ionomer cement in terms of surface microhardness and MEV. Materials and methods: Two CIVMR were provided and handled according to each manufacturer Vitremer (3M (ESPE) / St Paul / United States) and Riva Light Cure (SDI / Victoria / Australia). The CHX was incorporated into the liquid of each material in concentrations of 05%, 1% and 2%. Specimens were made with 4 mm in diameter and 2 mm in thickness, and divided according to the concentration of CHX and storage time (2, 7 and 30 days) in a total of eight groups with n = 10. Making the CP were immersed in saline, stored at 37 ºC. After 2, 7 and 30 days, they were submitted to Knoop microhardness. Results: Regarding microhardness, in 2 days of storage the Riva Light Cure 2% concentration showed higher values. Vitremer revealed significant differences between 1 and 2%. MEV analysis indicated a smoother surface for Riva Light Cure 1% after 30 days. Conclusion: CHX did not affect the microhardness properties of the studied CIVs. Vitremer showed superior behavior in most concentrations compared to Riva Light Cure. MEV showed that the immersion time caused more changes in the surface than the addition of CHX.